2017
DOI: 10.1292/jvms.17-0229
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning of canine Wilms’ tumor 1 for immunohistochemical analysis in canine tissues

Abstract: Wilms’ tumor 1 (WT1) expression has been investigated in various human cancers as a target molecule for cancer immunotherapy. However, few studies have focused on WT1 expression in dogs. Firstly, cDNA of canine WT1 (cWT1) was molecularly cloned from normal canine kidney. The cross-reactivity of the anti-human WT1 monoclonal antibody (6F-H2) with cWT1 was confirmed via Western blotting using cells overexpressing cWT1. Immunohistochemical staining revealed that cWT1 expression was detected in all canine lymphoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 19 publications
1
6
1
Order By: Relevance
“…In our study, we observed a lack of staining in lymphoma CTBs, whereas Sakai et al recently reported positivity in 22 cases of canine lymphoma, using the same monoclonal antibody. This controversy could be due to the cytoplasmic vs nuclear WT1 staining patterns.…”
Section: Discussioncontrasting
confidence: 71%
See 4 more Smart Citations
“…In our study, we observed a lack of staining in lymphoma CTBs, whereas Sakai et al recently reported positivity in 22 cases of canine lymphoma, using the same monoclonal antibody. This controversy could be due to the cytoplasmic vs nuclear WT1 staining patterns.…”
Section: Discussioncontrasting
confidence: 71%
“…Differences between WT1 polyclonal and monoclonal antibodies are well known, but recently immunostains performed with polyclonal antibodies did not correlate with WT1 gene expression in human tissues . Apparently, this problem also occurs in dogs, since multiple nonspecific bands were obtained in the Western blots with the WT1 polyclonal antibodies, which contrasted with a single 50‐55 kDa band (the expected molecular weight of WT1 protein) obtained with the monoclonal antibody used in this study …”
Section: Discussionmentioning
confidence: 59%
See 3 more Smart Citations